Biochemical Markers, Trace Elements, and Vitamins in Cutaneous Leishmaniasis - Noor Talal Ali; Shahad Saad Daham; Lubna Arkan Yonis; Abdul Rahman Jihad Mansour (Academia Open, 2025)
General Background: Cutaneous leishmaniasis is a prevalent parasitic disease in endemic regions and is increasingly recognized as a systemic condition associated with metabolic and nutritional disturbances beyond skin manifestations. Specific Background: Alterations in liver function, lipid metabolism, trace elements, and vitamin status have been reported in parasitic infections; however, integrated biochemical and molecular evidence in cutaneous leishmaniasis remains limited. Knowledge Gap: There is insufficient empirical data linking molecular identification of Leishmania species with comprehensive biochemical, trace element, and vitamin profiles in affected patients. Aims: This study aimed to evaluate biochemical markers, trace elements, and vitamins in patients with cutaneous leishmaniasis and to confirm Leishmania species using PCR. Results: Compared with controls, patients showed significantly elevated liver enzymes (AST, ALT, ALP) and lipid parameters, reduced iron and zinc levels, increased copper levels, and significantly lower vitamin D3 and B12 concentrations. Nested PCR identified Leishmania tropica as the predominant species, followed by L. major. Novelty: The study integrates serological, nutritional, and molecular data, providing a holistic profile of systemic alterations associated with cutaneous leishmaniasis. Implications: These findings underscore the importance of biochemical and nutritional monitoring alongside molecular diagnosis to improve clinical management and therapeutic strategies for cutaneous leishmaniasis.Highlight : Cutaneous leishmaniasis was associated with significant elevations in liver enzymes and serum lipid levels compared to controls. Marked alterations in trace elements were observed, characterized by reduced iron and zinc levels alongside increased copper concentrations. Patients exhibited significantly lower vitamin D3 and B12 levels, indicating a potential link between nutritional status and disease severity. Keywords : Leishmania, Liver Enzymes, Lipid Profile, Trace Elements, Vitamins